Determinan Akuntabilitas Pengelolaan Dana Desa Di Kota Denpasar - Suardyana, Luh Kalpika Jyunda A.; Rana Prasta, I Putu Agus; Merawati, Luh Komang; Endiana, I Dewa Made; Sunarsih, Ni Made (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
Increasing village fund allocation requires accountability in village fund management. This study aims to examine the internal characteristics of village fund managers, namely the competence of village government officials and organizational commitment as well as the Â internal control system and public participation in managing the village fund. The population of this study included village apparatus and BPD in 27 villages of Denpasar city. The data analysis technique used is multiple linear regression.The results show that competence of village government officials, organizational commitment, and public participation do not affect village fund management accountability, while the internal control system is found to have a positive effect significantly.Â